2015
DOI: 10.1186/s12978-015-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Fertility desire and associated factors among clients on highly active antiretroviral treatment at finoteselam hospital Northwest Ethiopia: a cross sectional study

Abstract: BackgroundThe accessibility of antiretroviral treatment changed the lives of persons living with HIV from hopelessness to hopefulness. Thus, many of them decided to have children. In Ethiopia, where there is high prevalence of HIV, level of fertility desire among persons living with HIV could have significant part in safe motherhood and child health. The aim of this study was to assess the level of fertility desire and identify factors associated with it among clients on highly active antiretroviral treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 10 publications
4
20
3
Order By: Relevance
“…This is similar to the studies conducted in South Florida (39%), Northeast Brazil (40%), Malawi (33.3%), Tanzania (37.1%)(21), Southwest Ethiopia (40.3%) (22)(23)(24)(25)(26). But, higher than the ndings in Atlanta (29.4%), West Gojjam Ethiopia (33.4%) (27,28). The difference might be due to sample size differences, difference in target population, the study in Atlanta took the samples only less than one third of the sample sizes of this study.…”
Section: Discussionsupporting
confidence: 86%
“…This is similar to the studies conducted in South Florida (39%), Northeast Brazil (40%), Malawi (33.3%), Tanzania (37.1%)(21), Southwest Ethiopia (40.3%) (22)(23)(24)(25)(26). But, higher than the ndings in Atlanta (29.4%), West Gojjam Ethiopia (33.4%) (27,28). The difference might be due to sample size differences, difference in target population, the study in Atlanta took the samples only less than one third of the sample sizes of this study.…”
Section: Discussionsupporting
confidence: 86%
“…This is similar to prior findings among South African women (Kaida et al, 2011) and in the aforementioned meta-analysis (Berhan and Berhan, 2013). Some studies, however, have found being on ART to be correlated with increased childbearing intention (Abbawa et al, 2015; Asfaw and Gashe, 2014; Cooper et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Some prior research has found a history of giving birth to be associated with decreased prospective childbearing intention among HIV-infected women (Abbawa et al, 2015; Asfaw and Gashe, 2014; Kawale et al 2014; Melaku et al, 2014). A study of HIV-infected Ghanaian women, however, found childbearing intention to be positively associated with a history of childbearing (Gyimah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming the prevalence of fertility desire (54.6%) from a study conducted in Addis Ababa Ethiopia [18], considering 95% confidence interval (CI),5% marginal error and considering 5% none response rate. The calculated sample size was 400 Sample size for factors associated with fertility desire was calculated using double proportion formula by Epi info version 7 with the following assumption: the significant variables associated with fertility desire were number current living child, age of client, fertility discussion with ART provider and duration on ART [19],95% confidence interval, power 80, ratio 1:1, and 5% none response rate.…”
Section: Sample Size Determinationmentioning
confidence: 99%